Effect of vitreomacular adhesion and vitreous gel on age-related reduction of macular thickness: a retrospective observational study. Issue 9 (30th September 2016) - Kumagai, Kazuyuki; Hangai, Masanori; Furukawa, Mariko; Suetsugu, Tetsuyuki; Ogino, Nobuchika
Abstract : Objective: To investigate the effects of vitreomacular adhesion (VMA), vitreomacular separation (VMS) and absence of vitreous gel due to vitrectomy on macular thickness measured in the spectral domain optical coherence tomographic (SD-OCT) images. Design: A longitudinal, retrospective, observational study. Setting: Secondary multicentre study. Participants: 218 eyes of 218 healthy patients and 119 vitrectomised eyes of 119 patients were studied. The healthy individuals were classified into a VMA group (54 eyes) and a VMS group (164 eyes), while the vitrectomised patients were classified into an internal limiting membrane (ILM)-on group (26 eyes) and an ILM-off group (93 eyes). In all participants, 2 Cirrus HD-OCT recordings were made with an average interval of 36 months (range 24–60 months). Primary and secondary outcome measures: The primary outcome measure was the rate of change in macular thickness in the central sector. The secondary outcomes were the rates of change in macular thickness in the inner 4 sectors. Results: The annual rate of change in the macular thickness of the central sector was 0.76±1.8 µm/year in the VMA group, −0.58±2.3 µm/year in the VMS group, −1.57±1.9 µm/year in the ILM-on group and −0.86±3.1 µm/year in the ILM-off group. There was a significant difference between the rate of the central sector thickness change in the VMA and VMS groups (p=0.0001). The presence of VMA was a significant factor associated with an increase in the central sector thickness (p=0.0055). When the healthy and ILM-on groups were compared, the rate of decrease in the central sector thickness was faster in the ILM-on group (p=0.0043). Multiple regression analyses showed that not peeling the ILM during the vitrectomy was a significant factor associated with a decrease in the central sector thickness (p=0.044). Conclusions: The presence of a VMA and a vitreous gel may help restrain the macular thickness reduction.